Chromaffin and sustentacular cells in the adrenal medulla of the viscacha (Lagostomus maximus maximus): A histochemical and immunohistochemical study - Gallol, Luis Ezequiel (2017)
Chromaffin and sustentacular cells are common components of the adrenal medulla of mammalian species. However, subpopulations of these cells varies among the different species. While the rat adrenal medulla is known to contain noradrenergic chromaffin cells in close relation with GFAP (glial fibrillary acidic protein)-positive sustentacular cells (SC-GFAP) other species express only chromaffin cells with an adrenergic phenotype and lack of SC-GFAPir. The aim of this study is to assess the distribution of adrenergic and noradrenergic chromaffin cells and SC-GFAPir in the adrenal medulla of the viscacha. Four male viscachas (N=4) and four male rats (N=4; technique control) were used in this study. In order to study the presence of adrenergic and noradrenergic chromaffin cells in the adrenal medulla, we used the histochemical method described by Honoré. The presence of SC-GFAPir was study by immunohistochemistry using an antibody against GFAP. In our study, the histochemical detection of noradrenergic chromaffin cells was negative throughout the adrenal medulla of the viscacha suggesting an adrenergic phenotype for this species, while the rat adrenal medulla used as control showed a strong positive reaction. The immunohistochemical detection of SC-GFAPir was also negative in the viscacha. These results showed that the viscacha adrenal medulla contains only chromaffin cells with an adrenergic phenotype and lack of SCGFAPir. This study is in accordance and contributes with the current literature adding another observation that suggests that SC-GFAPir are only expressed in presence of chromaffin cells with a noradrenergic phenotype. However, further studies are necessary to confirm this relation.